2009
DOI: 10.1063/1.3081031
|View full text |Cite
|
Sign up to set email alerts
|

Surface-enhanced fluorescence from metal sculptured thin films with application to biosensing in water

Abstract: Surface-enhanced fluorescence from porous, metallic sculptured thin films ͑STFs͒ was demonstrated for sensing of bacteria in water. Enhancement factors larger than 15 were observed using STFs made of silver, aluminum, gold, and copper with respect to their dense film counterparts. The STFs used are assemblies of tilted, shaped, parallel nanowires prepared with several variants of the oblique-angle-deposition technique. Comparison between the different films indicates that the enhancement factor is higher when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
61
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 21 publications
(21 reference statements)
1
61
0
Order By: Relevance
“…Surface-enhanced fluorescence from porous, metallic sculptured thin films (STFs) was demonstrated for sensing of bacteria in water by Abdulhalim et al [163] Enhancement factors larger than 15 were observed using STFs made of silver, aluminum, gold, and copper with respect to their dense-film counterparts. The STFs used are assemblies of tilted, shaped, parallel nanowires prepared with several variants of the oblique-angle-deposition technique (OAD).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Surface-enhanced fluorescence from porous, metallic sculptured thin films (STFs) was demonstrated for sensing of bacteria in water by Abdulhalim et al [163] Enhancement factors larger than 15 were observed using STFs made of silver, aluminum, gold, and copper with respect to their dense-film counterparts. The STFs used are assemblies of tilted, shaped, parallel nanowires prepared with several variants of the oblique-angle-deposition technique (OAD).…”
mentioning
confidence: 99%
“…The STFs used are assemblies of tilted, shaped, parallel nanowires prepared with several variants of the oblique-angle-deposition technique (OAD). Abdulhalim et al [163] examined the effect of the substrate material, constituent rods material, porosity, and the rods tilt angle on the enhancement factor of SEF. Enhancement of SEF from porous, metallic STFs was applied to biosensing in water.…”
mentioning
confidence: 99%
“…0.5-to 5-fold increase of the fluorescence intensity can be achieved. [31,32] Here, we demonstrate that our continuous gold wrinkled substrate is useful for MEF as well. Figures 3c and d (top) show fluorescence images along with the corresponding intensity profiles of dyes, dissolved in polymer solution and then spin-coated on either a bare glass plate or uniaxial gold wrinkles.…”
mentioning
confidence: 99%
“…[34] Compared with results from other continuous gold film nanostructures, a 7-fold enhancement is a significant achievement. [31,32] If the geometry of wrinkles is optimized, the critical spacing between the fluorophore and substrate controlled, and the density of intense hotspots increased, an average fluorescence intensity increase by at least one order of magnitude can be achieved. One potential MEF application is to improve the sensitivity of DNA and protein microarrays, in which high density probes with spot sizes from 10 to 500 mm are immobilized on substrates with areas of several square centimeters.…”
mentioning
confidence: 99%
“…The simplicity of this deposition technique with its ability to ''tailor'' the morphology of nanostructured thin films of various materials makes this deposition approach an ideal candidate for the fabrication of functional thin films whose functionality is based on the morphological dependence of various physical properties. Applications of glancing angle deposited thin films include square spiral photonic crystals [10][11][12], polarization filters [13], polarized light emitters [14], broadband antireflection coatings [15,16], narrow bandpass optical filters [17], high-speed humidity sensors [18], high sensitivity surface enhanced Raman spectroscopy [19][20][21] or surface enhanced fluorescence [22] substrates, and biomimetization [23], to name only a few.…”
mentioning
confidence: 99%